Association of frequent intradialytic hypotension with the clinical outcomes of patients on hemodialysis: a prospective cohort study - Yuanhao Wu; Jianda Lu; Tingting Wang; Xiaoye Zhu; Jun Xue; Li You (Renal Failure)
Intradialytic hypotension (IDH) is a common complication of hemodialysis (HD), but there is no consensus on its definition. In 2015, Flythe proposed a definition of IDH (Definition 1 in this study): nadir systolic blood pressure (SBP) <90 mmHg during hemodialysis for patients with pre-dialysis SBP <159 mmHg, and nadir SBP <100 mmHg during hemodialysis for patients with pre-dialysis SBP ≥160 mmHg. This prospective observational cohort study investigated the association of frequent IDH based on Definition 1 with clinical outcomes and compared Definition 1 with a commonly used definition (nadir SBP <90 mmHg during hemodialysis, Definition 2). The incidence of IDH was observed over a 3-month exposure assessment period. Patients with IDH events ≥30% were classified as ‘frequent IDH’; the others were ‘infrequent IDH’. All-cause mortality, cardiovascular mortality, and all-cause hospitalization events were followed up for 36 months. This study enrolled 163 HD patients. The incidence of IDH was 11.1% according to Definition 1 and 10.5% according to Definition 2. The Kaplan-Meier curves showed that frequent IDH patients had higher risks of all-cause mortality (p = 0.009, Definition 1; p = 0.002, Definition 2) and cardiovascular mortality (p = 0.021, Definition 1). Multivariable Cox regression analysis indicated that frequent IDH was independently associated with a higher risk of all-cause mortality (Model 1: HR = 2.553, 95%CI 1.334–4.886, p = 0.005; Model 2: HR = 2.406, 95%CI 1.253–4.621, p = 0.008). In conclusion, HD patients classified as frequent IDH are at a greater risk of all-cause mortality. This highlights the significance of acknowledging and proactively managing frequent IDH within the HD patients.